Collessiama (Diptera: Therevidae: Agapophytinae: Taenogera genus-group), a new genus from eastern Australia, with a key to the Australian genera of Therevidae - Lambkin, Christine L.; Turco, Federica (Zootaxa, 2013)
The stiletto fly family Therevidae is diverse and species rich in Australasia, with numerous undescribed species. Ongoing studies of Ectinorhynchus Macquart, 1850 from the Taenogera genus-group indicate that the genus Evansomyia Mann, 1928 stat. rev. is valid and is raised from synonymy for three species: Evansomyia phyciformis (White, 1915) stat. rev., Evansomyia scutellus (Mann, 1933) comb. nov., and Evansomyia venusta (Erichson, 1842) comb. nov.. Two new species of an unusual new therevid genus, Collessiama Lambkin gen. nov., are described from females and rare males collected in montane localities in eastern Australia. The dichotomous key to Australian therevid genera is updated to include Evan-somyia and Collessiama, and a key to species of Collessiama is provided. Collessiama narelleae Lambkin sp. nov. and Collessiama damani Lambkin sp. nov. are illustrated with drawings and high-resolution photographs of adult males and females, and genitalia. Detailed locality records are given for each species and distribution maps are provided.